DIGITAL STORYTELLING AS A MEDIUM OF DIALOGIC COMMUNICATION IN PUBLIC RELATIONS LEARNING IN DISTANCE EDUCATION - Alexander Mamby Aruan; Mirza Ronda; Dewi Widowati (International Journal of Social Science, 2026)
This study aims to examine and analyze differences in employee performance The development of digital technology has brought significant changes to learning processes in higher education, particularly within distance education systems. Although digital-based learning facilitates easier access to information, online learning practices often remain one-directional and provide limited opportunities for dialogue between lecturers and students. This study aims to analyze the role of the digital storytelling method in fostering dialogic communication in Public Relations learning within a distance education system. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observations of the learning process, and document analysis of students’ digital storytelling projects. The findings indicate that the implementation of digital storytelling enhances student engagement in the learning process, encourages reflective dialogue between lecturers and students, and develops students’ creative communication skills. This method also provides opportunities for students to express their experiences and critical perspectives through digital narratives. The findings suggest that digital storytelling can serve as an effective pedagogical strategy in fostering dialogic communication in distance learning within the field of Public Relations. Therefore, the integration of digital storytelling methods into digital learning environments can support the creation of a more participatory, reflective, and meaningful educational process.